Production and quality of the sainfoin forage (Onobrychis viaiaefolia Scop.) as affected by cutting regime in a hilly area of southern Italy - De Falco E.; Landi G.; Basso F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
This paper reports on the results of a research study aimed at evaluating both forage yield and quality of two sainfoin cultivar (variety 'Fakir' and the ecotype 'Firenzuola') under two cutting regimes: traditional (cutting at flowering + regrowth) and intensive (cutting at 30 cm of vegetation height). The trial was conducted in a hilly area of Basilicata on a 2 year old crop. Forage yield, leaf area, chemical composition and nutritional value of the forage were determined for each utilisation on both cultivar in spring 1996. Two cuts were given under the traditional rhythm and three cuts under the intensive rhythm. High temperatures at the beginning of summer interrupted regrowth in both systems. The highest yields were obtained with cutting at flowering, and cv. Fakir gave the highest value. Protein content was higher in early cuts of the intensive cutting regime.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)